Determinants of business cycle synchronization in North America - Anguiano Pita, Javier Emmanuel; Ruiz Porras, Antonio (Estudios de Economía, 2022)
This article analyzes the role of trade and financial integration, productive specialization and monetary policies in the synchronization of business cycles in North America from a long-run perspective. For this purpose, we estimate seemingly unrelated regression (SUR) models and Granger causality tests with annual panel data for Canada, the United States and Mexico during the period 1980-2019. The main findings suggest that: 1) trade integration has a positive effect and productive specialization a negative one on business cycle synchronization of the economies; 2) intra-industrial trade predominates in the region; 3) trade and financial integration processes are complementary; 4) financial integration promotes productive specialization; and, 5) progresses in trade and financial integration within the region are heterogeneous.